Survey suggests rising risk of food and nutrition insecurity in Addis Ababa, Ethiopia, as COVID-19 restrictions continue - Hirvonen, Kalle; Abate, Gashaw T.; de Brauw, Alan (International Food Policy Research Institute, 2020)
To cast light on how households in Addis Ababa, Ethiopia, are reacting to the crisis, IFPRI’s Ethiopia Strategy Support Program (ESSP), with the support of the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH), has begun a series of monthly phone surveys. Initial data demonstrate that poorer households are taking a greater economic hit than those with higher incomes, and that dietary diversity has declined. The results suggest the food security situation in Addis Ababa could sharply deteriorate in the coming weeks if disease transmission and social distancing measures continue.